Asian Culture, Diplomacy and Foreign Relations, Volume I - Wei, C. X. George, author.
1 online resource.
Keywords: Considering the important impact of Asian cultures on international relations, we conducted a multifaceted analysis and authentic summary of the Asian experiences and patterns of dealing with foreign relations from an Asian insider's perspective, aiming to find out where the diverging or converging diplomatic ways of the West and the East came from and what the positive diplomatic values and practices originated from Asian traditions are. Focusing on China, volume one thoroughly analyses the nature, political culture and mechanism of the tribute system from ancient time to the modern era within and beyond China. Volume two studies the culture and diplomacy of various individual Asian nations except for China, both in general and in particular cases, with an interdisciplinary approach. 考慮到亞洲文化對國際關係之影響的特殊重要性, 我們從一個亞洲局内人的角度, 對亞洲處理對外關係的經歷和模式進行了多方面的分析和真實可信的總結, 以發現在哪裏東西方的外交方式出現了分歧或聚合, 以及什麽是源於亞洲傳統的具有積極意義之外交價值觀. 卷一集中于中國, 徹底分析了朝貢體系的本質, 政治文化及其從古至近代以及在中國境外的延申和演變. 卷二以跨學科的方式, 探討了除中國以外亞洲各國不同的文化和外交, 既有綜合分析, 也有個案研究.